Analisis Strategi Pengembangan Usaha Koperasi Kopi Amungme Gold (Jurnal Agribisnis Indonesia, 2024)
The success of the Amungme Gold Coffee Cooperative as a business actor can be influenced by the business model that has been used so far. The Amungme Gold Coffee Cooperative produces Amungme Gold Coffee products, which the Amungme people traditionally cultivate. This study aims to determine the cooperative’s business model, internal and external conditions, and analyze the design of a new and to analyze the design of a new business model to develop the Amungme Gold Coffee Cooperative using the interview method with internal cooperatives and consumers who have bought and consumed Amungme Gold coffee. The data were analyzed using the descriptive business model method the Amungme Gold Coffee Cooperative currently uses and mapped using the Business Model Canvas. Each BMC element is identified using SWOT to determine strengths, weaknesses, opportunities and threats to produce alternative strategies that the Amungme Gold Coffee Cooperative can use. The SWOT analysis results become a reference for analysis with a four-step analysis of the blue ocean strategy to produce alternative strategies for the new BMC. The results of the study indicate that there is a need for a change in business strategy at the Amungme Gold Coffee Cooperative. So several strategies are recommended: adding new business units and creating an educational cafe concept, customer service using online media, developing warehousing facilities, and increasing training and mentoring farmers in cultivation activities.